Scalability and routing performance of future autonomous networks. (1st January 2013) - Palma, David; Curado, Marilia
The increasing availability of wireless gadgets motivated the development of autonomous networks and protocols. In addition to typical rural and disaster scenarios, dense urban areas must also be considered for mobile ad hoc networks. Handling a large number of decentralised wireless nodes raises several scalability issues. Even though routing solutions resort to clustering and hierarchies in order to limit the dissemination of routing information, nodes' interactions and mobility are typically disregarded. In this work, the scalability of three routing protocols is analysed, defining different network size scenarios, while assessing their routing performance with mobility. This assessment includes simulation-based results as well as a theoretical analysis of the impact of different hierarchical transitions. This evaluation's contribution reveals that the scalability of hierarchical organisations is closer to what is theoretically expected, contrary to non-hierarchical solutions. Moreover, the obtained results confirm the potential of future autonomous and ubiquitous networks.